Socio-Political Suppression of Female Identity in Nayantara Sahgal’s Rich Like Us - Ms. Divya Sharma, Nitin Bhatnagar (International Journal of Advanced Science and Technology, 2020)
The Indian emergency of 1975 was, and even today, remembered for reversal of the spirit of the independent era and the exploitation of the essence of humanism. The political pretext was used to employ force on common man and to use vengeance to settle political and personal issues. Nayantara Sahgal, through her explorations in Rich Like Us, deals with the far reaching effects of national political upheavals and of social set-up on the professional, social and personal life of common citizens, especially women. She deals with this issue from a feminist perspective as she employs these factors to portray the crushing of the modern Indian female consciousness. Using the novel as a medium, the paper is an attempt to study the impact of political turmoil, coupled with the prevailing social norms, on a woman’s identity and her struggle to safeguard her self-esteem. At the same time, there is an endeavor to study the contemporary relevance of the novelist’s vision of an emancipated woman.